Pengaruh Kompleksitas Auditor, Profesionalisme Auditor, dan Whistleblower terhadap Efektifitas Kemampuan Auditor dalam Pembuktian Kecurangan - Meri Yanti; Putri Nurmala (Universitas Pamulang, 2020)
This study aims to determine the effect of auditor complexity, auditor professionalism and whistleblower on the effectiveness of auditors' ability to prove fraud in representatives of public accounting firms (KAP) in South Tangerang and South Jakarta. This type of research is quantitative research with the number of samples taken as many as 35 respondents and 8 (eight) KAP. The sampling method used in this study is convenience sampling, which means selecting a sample that is easy to contact, easy to contact, easy to measure and cooperative in nature. The analysis used in this research is descriptive statistical analysis, data quality test, classical assumption test and hypothesis test which calculations are carried out using SPSS. The respondents are managers, supervisors, senior auditors and junior auditors. The results of this study indicate that auditor complexity and auditor professionalism do not have a significant effect on the effectiveness of the auditor's ability to prove fraud. While whistleblowers have a significant effect on the effectiveness of auditors' ability to prove fraud.Keywords: Complexity; Professionalism; Whistleblower; Proof of Fraud